Ceramic material, ceramic element and preparation methods of ceramic material and ceramic element

By adding LaScO3 and BiScO3 to the antiferroelectric ceramic materials, the antiferroelectric-ferroelectric phase change field is adjusted, and the problems of low energy density and capacitance of existing capacitor materials are solved, and ceramic capacitor materials with high energy storage density, strong breakdown field and high dielectric constant are achieved.

CN119551983AActive Publication Date: 2025-03-04KUNSHAN QINGYUAN ELECTRONIC TECHNOLOGY CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411741549.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-03-04
Estimated Expiration
2044-11-29

AI Technical Summary

Technical Problem

The energy density and capacitance of existing capacitor materials are low, and it is difficult to maintain a large dielectric constant and capacitance at high voltages, and the breakdown field strength is insufficient.

Method used

Antiferroelectric-shun-ferroelectric ternary solid solution ceramic material is used, with the chemical formula of (1-x-y)PbZrO3-xLaScO3-yBiScO3. The antiferroelectric-ferroelectric phase change field is adjusted by adding LaScO3 and BiScO3 materials to improve polarization strength and energy storage density.

Benefits of technology

The energy storage density, breakdown field strength and relative dielectric constant of the capacitor material are significantly improved, and the capacitance and performance of the capacitor are improved.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses an antiferroelectric-paraelectric-ferroelectric ternary solid solution ceramic material, the chemical formula of the ceramic material is (1-x-y) PbZrO3-xLaScO3-yBiScO3, x + y is less than or equal to 0.7, and x is more than 0 and less than or equal to 0.3. By adding LaScO3 and BiScO3 materials and controlling the mixing amount of the LaScO3 and BiScO3 materials, an anti-ferroelectric-ferroelectric phase change field can be adjusted in a larger range, and when the electric field is increased to an anti-ferroelectric-ferroelectric conversion electric field, the polarization intensity is rapidly increased, so that the effective energy storage density is rapidly increased, and the capacitance and the energy storage performance of the capacitor material are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of ceramic materials, in particular to a solid solution ceramic material, and in particular to an antiferroelectric-paraelectric-ferroelectric ternary solid solution ceramic material, a ceramic component, and a preparation method of the ceramic material and the ceramic component. Background Art

[0002] In order to meet the growing demand for high-voltage pulse and high-current generators in nuclear physics, electron beams, accelerators, lasers and other fields, energy storage capacitors have shown a development trend of miniaturization, integration, modularization and high reliability in recent years. Among them, capacitors with antiferroelectric ceramic materials as dielectrics are considered to have unique advantages in the above-mentioned fields with strict requirements on device miniaturization and reliability due to their advantages such as high energy storage density, stable performance and strong anti-electromagnetic interference ability. They are ideal materials for preparing energy storage capacitors.

[0003] Currently, commercially used dielectric capacitors are mainly made of dielectric polymers or dielectric ceramics, and their energy density is about 10 -2 ~10 -1 Wh / kg(less than 2J / cm 3 ). Compared with traditional dielectric capacitors, electrochemical supercapacitors have moderate energy density, but their power density still cannot meet the application requirements of ultra-high power devices and systems such as hybrid vehicles, electron guns, etc. Therefore, if the energy storage density of dielectric capacitors can be improved to the level of electrochemical supercapacitors or even batteries, their application areas will be greatly expanded. Dielectric capacitors with high energy storage density will further promote the development of electronic and electrical systems towards miniaturization, lightweight and integration. At the same time, ceramic dielectric capacitors have good mechanical and thermal properties and are the most critical energy storage components for pulse power technology.

[0004] The research on antiferroelectric ceramic materials can be traced back to the 1950s and 1960s. Since the phase transition field strength of lead zirconate (PbZrO3) antiferroelectric ceramics is relatively high and double hysteresis loops cannot be excited at room temperature, antiferroelectric ceramic materials with lead zirconate titanate (Pb(Zr,Ti)O3, PZT) solid solution as the main crystal phase have been developed. These solid solution materials include PZT antiferroelectric ceramic materials with a zirconium-titanium molar ratio of about 95 / 5, which can undergo ferroelectric-antiferroelectric phase transition under certain external conditions such as temperature, stress and electric field. However, the antiferroelectric phase region of this system is relatively small, and it is very easy to fail to undergo phase transition due to component deviation during the material synthesis process. In addition, the antiferroelectric phase of PZT95 / 5 material can only be transformed into a ferroelectric phase under high temperature and strong electric field, which also restricts the application of this material. Therefore, this binary system is not suitable for making antiferroelectric ceramic energy storage capacitor materials. Summary of the invention

[0005] The present invention provides a ceramic material which can be used in ceramic energy storage capacitors to solve the problems of low energy density and capacitance of existing capacitor materials, and can still maintain a large dielectric constant and capacitance under a higher voltage, while further improving the breakdown field strength of the capacitor.

[0006] In a first aspect, the present invention provides an antiferroelectric-paraelectric-ferroelectric ternary solid solution ceramic material, the chemical formula of which is: (1-xy)PbZrO3-xLaScO3-yBiScO3, wherein x+y≤0.7, 0<x≤0.3.

[0007] The antiferroelectric-paraelectric-ferroelectric ternary solid solution ceramic material provided by the present invention is based on antiferroelectric PbZrO3. By adding LaScO3 and BiScO3 materials, the antiferroelectric-ferroelectric phase transition field can be adjusted in a larger range. When the electric field is increased to the antiferroelectric-ferroelectric transition electric field, the polarization intensity rises rapidly, thereby sharply increasing the effective energy storage density, thereby improving the capacitance and energy storage performance of the capacitor material.

[0008] In a second aspect, the present invention provides a method for preparing an antiferroelectric-paraelectric-ferroelectric ternary solid solution ceramic material, the method comprising the following steps:

[0009] S1. According to the ceramic material described in the first aspect, bismuth oxide, lead carbonate, lanthanum oxide, scandium oxide and zirconium oxide are mixed in a stoichiometric ratio, and then ball milled;

[0010] S2, calcining the sample at 600-900°C for 2-5 hours, then ball-milling the calcined powder again, adding a binder to mix evenly, and pressing it into a disc, controlling the disc thickness to be 50 μm-1 mm;

[0011] S3, sintering the obtained disc at 1000-1500 degrees Celsius for 1-4 hours to obtain a sintered ceramic sheet material.

[0012] The present invention designs an antiferroelectric-ferroelectric-paraelectric ternary solid solution. By adopting the above-mentioned preparation process and adjusting the layer thickness, the rated voltage at the operating temperature is located near the antiferroelectric-ferroelectric transition field, thereby improving the relative dielectric constant and breakdown field strength under high voltage, and improving the capacitance and energy storage performance of the capacitor material.

[0013] In an optional embodiment, in the above step S2, the thickness of the disc is controlled to be 100-800 μm.

[0014] In an optional embodiment, in the above step S2, the calcination temperature is 700-850°C.

[0015] In an optional embodiment, in the above step S2, the calcination time is 3-4 hours.

[0016] In an optional embodiment, in the above step S3, the sintering temperature is 1100-1350°C.

[0017] In an optional embodiment, in the above step S3, the sintering time is 2-3 hours.

[0018] In a third aspect, the present invention provides a method for preparing a ceramic component, which comprises, after obtaining the ceramic material described in the second aspect, brushing silver on the upper and lower surfaces of the ceramic material and sintering at 700-900° C. for 10-30 minutes under a protective atmosphere to obtain the ceramic component.

[0019] In an optional embodiment, in the above steps, the sintering temperature is 800-850°C.

[0020] In an optional embodiment, in the above steps, the sintering time is 10 to 20 minutes.

[0021] In a fourth aspect, the present invention provides a ceramic component obtained by the preparation method described in the fourth aspect.

[0022] For the technical effects that may be achieved by the method for preparing the ceramic material disclosed in the second aspect, the method for preparing the ceramic component disclosed in the third aspect, and the ceramic component disclosed in the fourth aspect, please refer to the description of the technical effects that can be achieved by the first aspect or various possible schemes in the first aspect, and no repetition will be given here.

[0023] Other features and advantages of the embodiments of the present application will be described in detail in the subsequent specific implementation section. DETAILED DESCRIPTION

[0024] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention will be further described in detail below. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0025] As mentioned above, the traditional antiferroelectric ceramics of lead zirconate (PbZrO3) have a relatively high phase transition field strength and cannot excite double hysteresis loops at room temperature. However, the antiferroelectric ceramic materials with lead zirconate titanate (Pb(Zr,Ti)O3, PZT) solid solution as the main crystal phase can undergo ferroelectric-antiferroelectric phase transition under certain external conditions such as temperature, stress and electric field. However, the antiferroelectric phase region of this system is relatively small, and it is very easy to fail to undergo phase transition due to component deviation during the material synthesis process. In addition, the antiferroelectric phase of PZT95 / 5 material can only be transformed into a ferroelectric phase under high temperature and strong electric field, which also restricts the application of this material. In addition, antiferroelectric ceramics have an antiferroelectric phase-ferroelectric phase transition when an external electric field is applied, inducing a rapid increase in polarization intensity. When the external electric field is removed, the electric field-induced ferroelectric phase quickly transforms into an antiferroelectric phase, resulting in a residual polarization intensity that is almost zero. Therefore, only when the breakdown electric field strength of the antiferroelectric ceramic capacitor is higher than the antiferroelectric phase-ferroelectric phase transition electric field strength, can a higher energy density be obtained. Therefore, this technology aims to solve the problem of low energy density and capacitance of existing capacitor materials, and can still maintain a large dielectric constant and capacitance at a higher voltage, while further improving the breakdown field strength of the capacitor.

[0026] Based on this, the embodiment of the present invention provides an antiferroelectric-paraelectric-ferroelectric ternary solid solution ceramic material, the chemical formula of the ceramic material is: (1-xy)PbZrO3-xLaScO3-yBiScO3, wherein x+y≤0.7, 0<x≤0.3. The applicant takes antiferroelectric PbZrO3 as the basis, and by adding LaScO3 and BiScO3 materials, when the electric field increases to the antiferroelectric-ferroelectric transition electric field, the polarization intensity rises rapidly, thereby causing the effective energy storage density to increase sharply, and the antiferroelectric-ferroelectric phase transition conditions can be adjusted within a larger range to improve the performance of the material, thereby greatly improving the relative dielectric constant and breakdown field strength under high pressure, and improving the dielectric constant, capacitance and performance of the capacitor material. The applicant has found through experiments that when the content of paraelectric and ferroelectric materials is controlled at x+y≤0.7 and x≤0.3, the breakdown field strength of the prepared capacitor can be greatly improved, the dielectric constant and energy density under high pressure can be improved, and the capacitance and performance of the capacitor can also be improved.

[0027] In order to better understand the technical solution provided by the embodiment of the present invention, the following briefly introduces the application scenarios to which the technical solution provided by the embodiment of the present invention is applicable. It should be noted that the application scenarios introduced below are only used to illustrate the embodiment of the present invention and are not limited. In specific implementation, the technical solution provided by the embodiment of the present invention can be flexibly applied according to actual needs.

[0028] After introducing the application scenarios of the embodiments of the present invention, the preferred implementation modes of the present invention are further described in detail below. It should be understood that the preferred embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention. In addition, the embodiments of the present invention and the features in the embodiments may be combined with each other if there is no conflict.

[0029] In addition, although the embodiments of the present invention provide method operation steps as shown in the following embodiments, more or fewer operation steps may be included in the method based on routine or no creative labor. In the steps where there is no necessary causal relationship logically, the execution order of these steps is not limited to the endpoints of the ranges disclosed in this article and any values ​​are not limited to the precise ranges or values, which should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be regarded as specifically disclosed in this article. 。

[0030] The following is a detailed description of the method for preparing the ceramic material provided by the embodiment of the present invention.

[0031] A method for preparing an antiferroelectric-paraelectric-ferroelectric ternary solid solution ceramic material, the method comprising the following steps:

[0032] S1. Prepare raw materials according to the chemical formula (1-xy)PbZrO3-xLaScO3-yBiScO3 (wherein, x+y≤0.7, 0<x≤0.3), mix bismuth oxide, lead carbonate, lanthanum oxide, scandium oxide, and zirconium oxide raw materials according to the above stoichiometric ratio, and ball mill the mixed raw materials;

[0033] S2, calcining the sample at 600-900°C for 2-5 hours, then ball-milling the calcined powder again, adding a binder to mix evenly, and pressing it into a disc, controlling the disc thickness to be 50 μm-1 mm;

[0034] S3, sintering the obtained disc at 1000-1500 degrees Celsius for 1-4 hours to obtain a sintered ceramic sheet material.

[0035] In the above step S1, the (1-xy)PbZrO3-xLaScO3-yBiScO3 is a ternary solid solution, in which PbZrO3 with antiferroelectric properties is the main component, LaScO3 and BiScO3 as paraelectric and ferroelectric materials are solid-dissolved with antiferroelectric materials to form a ternary ceramic solid solution, and x+y≤0.7, 0<x≤0.3. In the above ball milling process, dry or wet ball milling process can be adopted. When wet ball milling is adopted, anhydrous ethanol is preferably used as the medium. The grinding ball is preferably zirconium oxide, and the specific ball milling equipment is not limited. The ball milling machine commonly used in powder engineering can be selected according to the needs to achieve the purpose of sufficient reaction of the raw materials. The above steps use the oxide or carbonate of the component as the raw material, but it is not limited to this. Other corresponding salts or oxide raw materials can also be used, and the calcination temperature and ball milling parameters can be adjusted accordingly.

[0036] In addition, preferably, the step of drying at 40° C. to 90° C. for 3-5 hours is also included after ball milling.

[0037] After drying, the sample can be calcined at 600-900°C for 2-5 hours. The purpose of this step is to remove the moisture of the raw material through pre-calcination treatment, and to improve the activity of the raw material. The composition and organizational structure of the raw material are improved through pre-calcination, so that the antiferroelectric phase is crystallized in advance, thereby improving the performance of the finished product. The above calcination temperature is preferably 700-850°C, and the calcination time is preferably 2-3 hours.

[0038] After the pre-sintering process is completed, the pre-sintered raw materials are ball-milled again to control the ball-milling process parameters. The secondary ball-milling can also be achieved by dry or wet methods. When wet ball-milling is used, anhydrous ethanol is preferably used as the medium. Zirconium oxide is also preferred for the grinding balls, and the specific ball-milling equipment is not limited. After the secondary ball-milling is completed, an adhesive is added, and the adhesive and the powder are mixed evenly. After that, the tablet press is used to press it into a disc shape, and the thickness of the disc is controlled to be 50 μm to 1 mm, preferably 100 to 800 μm. By adjusting the layer thickness to a suitable thickness, the rated voltage at the operating temperature can be located near the antiferroelectric-ferroelectric transition field. In the above bonding process, PVA and PEG are preferably used as adhesives.

[0039] After obtaining the pressed product, a subsequent sintering step can be performed. Specifically, the sample can be sintered at 1000-1500 degrees Celsius for 1-4 hours, and the sintering temperature is preferably 1100-1350 degrees Celsius and 2-3 hours. The sintering process can be a one-stage sintering process or a multi-stage step-by-step sintering process.

[0040] The step-by-step sintering can preferably adopt a three-stage sintering process. The first stage: sintering at 1000-1100℃ for 0.5-1 hour. At this stage, the particles in the raw materials are rearranged, bonding occurs at the contact points, and the voids are deformed and reduced. The second stage: sintering at 1100-1250℃ for 1-2 hours. At this stage, mass transfer begins, the grain boundaries increase, and the voids further deform and shrink, but still remain connected. The third stage: sintering at 1250-1400℃ for 2-3 hours. At this stage, mass transfer continues, the particles grow, the pores become isolated closed pores, and the density and product strength are significantly improved. Through the above three-stage sintering process, the heating and cooling processes can be accurately controlled, the microstructure and properties of the materials can be optimized, and the crystallization purity of the ceramic materials and the performance stability of the products can be improved.

[0041] In addition, during the sintering process, hot pressing sintering can be used. Compared with traditional solid-phase sintering, hot pressing sintering can reduce the sintering temperature, shorten the sintering time, and refine the grains. With the refinement of the grains, the breakdown electric field of the ceramic can be greatly increased. The preferred hot pressing pressure is 1.1 to 1.4 t.

[0042] Through the above sintering process, the desired antiferroelectric-ferroelectric-paraelectric ternary solid solution ceramic sheet is obtained. Further, by brushing silver on the upper and lower surfaces of the ceramic material and sintering at 700-900°C for 10-30 minutes under a protective atmosphere, a ceramic capacitor that can be used for energy storage is obtained. In order to further control the performance of the capacitor, the above sintering temperature and time are preferably 800-850°C and 10-20 minutes.

[0043] The above mentioned that the ternary solid solution ceramic material and ceramic capacitor are prepared by the solid phase sintering method, but the present invention is not limited to the solid phase sintering process. Plasma discharge sintering is also one of the preferred methods for preparing the above materials. The discharge plasma generated by the DC pulse current is used to promote the self-heating and surface activation of the powder to achieve the heating effect, and the heating and pressurization factors that can promote sintering are combined to greatly improve the relative density of the prepared ceramics, accelerate the heating rate, and reduce the sintering temperature and insulation time. Therefore, the use of plasma discharge sintering can correspondingly shorten the sintering temperature to 800-1100°C and shorten the sintering time to 0.5-2 hours. At the same time, only one-stage sintering can be used.

[0044] According to the process introduced above, representative embodiments are selected below and their related performances are tested.

[0045] Embodiment 1:

[0046] S1. Prepare raw materials according to the chemical formula 0.8PbZrO3-0.2BiScO3, mix bismuth oxide, lead carbonate, scandium oxide and zirconium oxide according to the above stoichiometric ratio, and pass through a 100-mesh sieve after wet ball milling;

[0047] S2, calcining the sample at 800°C for 3 hours, then ball-milling the calcined powder again and passing it through a 200-mesh sieve, adding PVA and PEG as binders, mixing evenly, and pressing into a disc, and controlling the disc thickness to be 500 μm;

[0048] S3. Hot-press and sinter the obtained disc at 1350 degrees Celsius for 2 hours, controlling the pressure to 1.2 tons, to obtain a sintered ceramic sheet material.

[0049] S4. Silver is applied to the upper and lower surfaces of the obtained ceramic sheet material and sintered at 800° C. for 15 minutes under a protective atmosphere to obtain a ceramic capacitor that can be used for energy storage.

[0050] The obtained capacitor material was tested to obtain its energy storage density W (J / cm 3 ), breakdown field strength E (kV / cm), and relative dielectric constant ε.

[0051] Embodiment 2:

[0052] S1. Prepare raw materials according to the chemical formula 0.7PbZrO3-0.1LaScO3-0.2BiScO3, mix bismuth oxide, lead carbonate, lanthanum oxide, scandium oxide and zirconium oxide according to the above stoichiometric ratio, and pass through a 100-mesh sieve after wet ball milling;

[0053] S2, calcining the sample at 800°C for 3 hours, then ball-milling the calcined powder again and passing it through a 200-mesh sieve, adding PVA and PEG as binders, mixing evenly, and pressing into a disc, and controlling the disc thickness to be 500 μm;

[0054] S3. Hot-press and sinter the obtained disc at 1350 degrees Celsius for 2 hours, controlling the pressure to 1.2 tons, to obtain a sintered ceramic sheet material.

[0055] S4. Silver is applied to the upper and lower surfaces of the obtained ceramic sheet material and sintered at 800° C. for 15 minutes under a protective atmosphere to obtain a ceramic capacitor that can be used for energy storage.

[0056] The obtained capacitor material was tested to obtain its energy storage density W (J / cm 3 ), breakdown field strength E (kV / cm), and relative dielectric constant ε.

[0057] Embodiment 3:

[0058] S1. Prepare raw materials according to the chemical formula 0.6PbZrO3-0.2LaScO3-0.2BiScO3, mix bismuth oxide, lead carbonate, lanthanum oxide, scandium oxide and zirconium oxide according to the above stoichiometric ratio, and pass through a 100-mesh sieve after wet ball milling;

[0059] S2, calcining the sample at 800°C for 3 hours, then ball-milling the calcined powder again and passing it through a 200-mesh sieve, adding PVA and PEG as binders, mixing evenly, and pressing into a disc, and controlling the disc thickness to be 500 μm;

[0060] S3. Hot-press and sinter the obtained disc at 1350 degrees Celsius for 2 hours, controlling the pressure to 1.2 tons, to obtain a sintered ceramic sheet material.

[0061] S4. Silver is applied to the upper and lower surfaces of the obtained ceramic sheet material and sintered at 800° C. for 15 minutes under a protective atmosphere to obtain a ceramic capacitor that can be used for energy storage.

[0062] The obtained capacitor material was tested to obtain its energy storage density W (J / cm 3 ), breakdown field strength E (kV / cm), and relative dielectric constant ε.

[0063] Embodiment 4:

[0064] S1. Prepare raw materials according to the chemical formula 0.5PbZrO3-0.3LaScO3-0.2BiScO3, mix bismuth oxide, lead carbonate, lanthanum oxide, scandium oxide and zirconium oxide according to the above stoichiometric ratio, and pass through a 100-mesh sieve after wet ball milling;

[0065] S2, calcining the sample at 800°C for 3 hours, then ball-milling the calcined powder again and passing it through a 200-mesh sieve, adding PVA and PEG as binders, mixing evenly, and pressing into a disc, and controlling the disc thickness to be 500 μm;

[0066] S3. Hot-press and sinter the obtained disc at 1350 degrees Celsius for 2 hours, controlling the pressure to 1.2 tons, to obtain a sintered ceramic sheet material.

[0067] S4. Silver is applied to the upper and lower surfaces of the obtained ceramic sheet material and sintered at 800° C. for 15 minutes under a protective atmosphere to obtain a ceramic capacitor that can be used for energy storage.

[0068] The obtained capacitor material was tested to obtain its energy storage density W (J / cm 3 ), breakdown field strength E (kV / cm), and relative dielectric constant ε.

[0069] Embodiment 5:

[0070] S1. Prepare raw materials according to the chemical formula 0.4PbZrO3-0.4LaScO3-0.2BiScO3, mix bismuth oxide, lead carbonate, lanthanum oxide, scandium oxide and zirconium oxide according to the above stoichiometric ratio, and pass through a 100-mesh sieve after wet ball milling;

[0071] S2, calcining the sample at 800°C for 3 hours, then ball-milling the calcined powder again and passing it through a 200-mesh sieve, adding PVA and PEG as binders, mixing evenly, and pressing into a disc, and controlling the disc thickness to be 500 μm;

[0072] S3. Hot-press and sinter the obtained disc at 1350 degrees Celsius for 2 hours, controlling the pressure to 1.2 tons, to obtain a sintered ceramic sheet material.

[0073] S4. Silver is applied to the upper and lower surfaces of the obtained ceramic sheet material and sintered at 800° C. for 15 minutes under a protective atmosphere to obtain a ceramic capacitor that can be used for energy storage.

[0074] The obtained capacitor material was tested to obtain its energy storage density W (J / cm 3 ), breakdown field strength E (kV / cm), and relative dielectric constant ε.

[0075] Embodiment 6:

[0076] S1. Prepare raw materials according to the chemical formula 0.3PbZrO3-0.5LaScO3-0.2BiScO3, mix bismuth oxide, lead carbonate, lanthanum oxide, scandium oxide and zirconium oxide according to the above stoichiometric ratio, and pass through a 100-mesh sieve after wet ball milling;

[0077] S2, calcining the sample at 800°C for 3 hours, then ball-milling the calcined powder again and passing it through a 200-mesh sieve, adding PVA and PEG as binders, mixing evenly, and pressing into a disc, and controlling the disc thickness to be 500 μm;

[0078] S3. Hot-press and sinter the obtained disc at 1350 degrees Celsius for 2 hours, controlling the pressure to 1.2 tons, to obtain a sintered ceramic sheet material.

[0079] S4. Silver is applied to the upper and lower surfaces of the obtained ceramic sheet material and sintered at 800° C. for 15 minutes under a protective atmosphere to obtain a ceramic capacitor that can be used for energy storage.

[0080] The obtained capacitor material was tested to obtain its energy storage density W (J / cm 3 ), breakdown field strength E (kV / cm), and relative dielectric constant ε.

[0081] The test results of the above embodiment are shown in the following table:

[0082] Table 1 Capacitor performance obtained in Examples 1-6

[0083] <![CDATA[W(J / cm 3 )]]> Breakdown field strength (kV / cm) Relative dielectric constant ε Example 1 10.2 453 677 Example 2 11.7 456 356 Example 3 13.5 558 301 Example 4 11.4 579 251 Example 5 10.5 516 223 Example 6 7.2 372 198

[0084] As shown in Table 1, it can be seen from the above Examples 1-6 that when paraelectric materials and ferroelectric materials are doped into antiferroelectric PbZrO3, the energy storage density of ceramic capacitors can be significantly improved, and its energy storage density can reach 13.5 J / cm 3 , and the breakdown field strength has also been significantly improved. Moreover, when the LaScO3 content is controlled below 0.3, the capacitor has the best comprehensive performance.

[0085] Embodiment 7:

[0086] S1, prepare raw materials according to the chemical formula PbZrO3, mix lead carbonate and zirconium oxide raw materials according to the above stoichiometric ratio, use wet ball milling and then pass through a 100 mesh sieve;

[0087] S2, calcining the sample at 800°C for 3 hours, then ball-milling the calcined powder again and passing it through a 200-mesh sieve, adding PVA and PEG as binders, mixing evenly, and pressing into a disc, and controlling the disc thickness to be 500 μm;

[0088] S3. Hot-press and sinter the obtained disc at 1350 degrees Celsius for 2 hours, controlling the pressure to 1.2 tons, to obtain a sintered ceramic sheet material.

[0089] S4. Silver is applied to the upper and lower surfaces of the obtained ceramic sheet material and sintered at 800° C. for 15 minutes under a protective atmosphere to obtain a ceramic capacitor that can be used for energy storage.

[0090] The obtained capacitor material was tested to obtain its energy storage density W (J / cm 3 ), breakdown field strength E (kV / cm), and relative dielectric constant ε.

[0091] Embodiment 8:

[0092] S1. Prepare raw materials according to the chemical formula 0.8PbZrO3-0.2LaScO3, mix lead carbonate, lanthanum oxide, scandium oxide and zirconium oxide according to the above stoichiometric ratio, and pass through a 100-mesh sieve after wet ball milling;

[0093] S2, calcining the sample at 800°C for 3 hours, then ball-milling the calcined powder again and passing it through a 200-mesh sieve, adding PVA and PEG as binders, mixing evenly, and pressing into a disc, and controlling the disc thickness to be 500 μm;

[0094] S3. Hot-press and sinter the obtained disc at 1350 degrees Celsius for 2 hours, controlling the pressure to 1.2 tons, to obtain a sintered ceramic sheet material.

[0095] S4. Silver is applied to the upper and lower surfaces of the obtained ceramic sheet material and sintered at 800° C. for 15 minutes under a protective atmosphere to obtain a ceramic capacitor that can be used for energy storage.

[0096] The obtained capacitor material was tested to obtain its energy storage density W (J / cm 3 ), breakdown field strength E (kV / cm), and relative dielectric constant ε.

[0097] Embodiment 9:

[0098] S1. Prepare raw materials according to the chemical formula 0.3PbZrO3-0.2LaScO3-0.4BiScO3, mix bismuth oxide, lead carbonate, lanthanum oxide, scandium oxide and zirconium oxide according to the above stoichiometric ratio, and pass through a 100-mesh sieve after wet ball milling;

[0099] S2, calcining the sample at 800°C for 3 hours, then ball-milling the calcined powder again and passing it through a 200-mesh sieve, adding PVA and PEG as binders, mixing evenly, and pressing into a disc, and controlling the disc thickness to be 500 μm;

[0100] S3. Hot-press and sinter the obtained disc at 1350 degrees Celsius for 2 hours, controlling the pressure to 1.2 tons, to obtain a sintered ceramic sheet material.

[0101] S4. Silver is applied to the upper and lower surfaces of the obtained ceramic sheet material and sintered at 800° C. for 15 minutes under a protective atmosphere to obtain a ceramic capacitor that can be used for energy storage.

[0102] The obtained capacitor material was tested to obtain its energy storage density W (J / cm 3 ), breakdown field strength E (kV / cm), and relative dielectric constant ε.

[0103] Embodiment 10:

[0104] S1. Prepare raw materials according to the chemical formula 0.3PbZrO3-0.2LaScO3-0.5BiScO3, mix bismuth oxide, lead carbonate, lanthanum oxide, scandium oxide and zirconium oxide according to the above stoichiometric ratio, and pass through a 100-mesh sieve after wet ball milling;

[0105] S2, calcining the sample at 800°C for 3 hours, then ball-milling the calcined powder again and passing it through a 200-mesh sieve, adding PVA and PEG as binders, mixing evenly, and pressing into a disc, and controlling the disc thickness to be 500 μm;

[0106] S3. Hot-press and sinter the obtained disc at 1350 degrees Celsius for 2 hours, controlling the pressure to 1.2 tons, to obtain a sintered ceramic sheet material.

[0107] S4. Silver is applied to the upper and lower surfaces of the obtained ceramic sheet material and sintered at 800° C. for 15 minutes under a protective atmosphere to obtain a ceramic capacitor that can be used for energy storage.

[0108] The obtained capacitor material was tested to obtain its energy storage density W (J / cm 3 ), breakdown field strength E (kV / cm), and relative dielectric constant ε at 10kV deflection voltage.

[0109] Embodiment 11:

[0110] S1. Prepare raw materials according to the chemical formula 0.2PbZrO3-0.2LaScO3-0.6BiScO3, mix bismuth oxide, lead carbonate, lanthanum oxide, scandium oxide and zirconium oxide according to the above stoichiometric ratio, and pass through a 100-mesh sieve after wet ball milling;

[0111] S2, calcining the sample at 800°C for 3 hours, then ball-milling the calcined powder again and passing it through a 200-mesh sieve, adding PVA and PEG as binders, mixing evenly, and pressing into a disc, and controlling the disc thickness to be 500 μm;

[0112] S3. Hot-press and sinter the obtained disc at 1350 degrees Celsius for 2 hours, controlling the pressure to 1.2 tons, to obtain a sintered ceramic sheet material.

[0113] S4. Silver is applied to the upper and lower surfaces of the obtained ceramic sheet material and sintered at 800° C. for 15 minutes under a protective atmosphere to obtain a ceramic capacitor that can be used for energy storage.

[0114] The obtained capacitor material was tested to obtain its energy storage density W (J / cm 3 ), breakdown field strength E (kV / cm), and relative dielectric constant ε at 10kV deflection voltage.

[0115] The test results of the above embodiment are shown in the following table:

[0116] Table 2 Capacitor performance obtained in Examples 3, 7-11

[0117] <![CDATA[W(J / cm 3 )]]> Breakdown field strength (kV / cm) Relative dielectric constant ε Example 7 3.3 231 202 Example 8 9.6 462 196 Example 3 13.5 558 301 Example 9 12.3 480 482 Example 10 10.5 453 524 Embodiment 11 9.6 378 511

[0118] As shown in Table 2, it can be seen from the above examples that when paraelectric materials and ferroelectric materials are doped into antiferroelectric PbZrO3, the energy storage density of ceramic capacitors can be significantly improved, and its energy storage density can reach 13.5 J / cm 3, and the breakdown field strength and relative dielectric constant have also been significantly improved, and the capacitor can still maintain a large dielectric constant and capacitance at a higher voltage. In addition, when the total doping amount of LaScO3 and BiScO3 is controlled below 0.7, the capacitor has the best comprehensive performance.

[0119] Although the preferred embodiments of the present invention have been described, those skilled in the art may make additional changes and modifications to these embodiments once they have learned the basic creative concept. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.

[0120] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.

Claims

1. An antiferroelectric-paraelectric-ferroelectric ternary solid solution ceramic material, characterized in that: The chemical formula of the ceramic material is: (1-xy)PbZrO3-xLaScO3-yBiScO3, wherein x+y≤0.7, 0<x≤0.

3.

2. A method for preparing the antiferroelectric-paraelectric-ferroelectric ternary solid solution ceramic material according to claim 1, characterized in that: The following steps are involved: S1, mixing bismuth oxide, lead carbonate, lanthanum oxide, scandium oxide and zirconium oxide raw materials according to a stoichiometric ratio, and ball milling the mixed materials; S2, calcining the sample at 600-900°C for 2-5 hours, then ball-milling the calcined powder again, adding a binder to mix evenly, and pressing it into a disc, controlling the disc thickness to be 50 μm-1 mm; S3, sintering the obtained disc at 1000-1500 degrees Celsius for 1-4 hours to obtain a sintered ceramic sheet material.

3. A method for preparing the antiferroelectric-paraelectric-ferroelectric ternary solid solution ceramic material according to claim 2, characterized in that: In the step S2, the thickness of the disk is controlled to be 100-800 μm.

4. A method for preparing the antiferroelectric-paraelectric-ferroelectric ternary solid solution ceramic material according to claim 2, characterized in that: In the step S2, the calcination temperature is 700-850°C.

5. A method for preparing the antiferroelectric-paraelectric-ferroelectric ternary solid solution ceramic material according to claim 4, characterized in that: In the step S2, the calcination time is 3-4 hours.

6. A method for preparing the antiferroelectric-paraelectric-ferroelectric ternary solid solution ceramic material according to claim 2, characterized in that: In the step S3, the sintering temperature is 1100-1350°C.

7. A method for preparing the antiferroelectric-paraelectric-ferroelectric ternary solid solution ceramic material according to claim 6, characterized in that: In step S3, the sintering time is 2-3 hours.

8. A method for preparing a ceramic component, characterized in that: The method comprises: after obtaining the ceramic material according to any one of claims 2 to 7, brushing silver on the upper and lower surfaces of the ceramic material and sintering at 700 to 900° C. for 10 to 30 minutes under a protective atmosphere to obtain the ceramic element.

9. A method for preparing the ceramic element according to claim 8, characterized in that: The sintering temperature under protective atmosphere is 800-850°C.

10. A method for preparing the ceramic element according to claim 8, characterized in that: The sintering time under protective atmosphere is 10 to 20 minutes.

11. A ceramic component obtained by the preparation method according to any one of claims 8 to 10.

Citation Information

Patent Citations

  • Bismuth scandate-lead titanate high-temperature piezoelectric ceramic material and preparation method thereof

    CN102180665A

  • PLZT-based antiferroelectric ceramic material with high energy storage density and preparation method and application thereof

    CN109665839A

  • Method for improving energy storage density of dielectric film capacitor and dielectric film capacitor

    CN113314342A

  • Lanthanum-doped scandium lead tantalate and lead titanate piezoelectric ceramic as well as preparation method and application thereof

    CN115636667A

  • Lead-based anti-ferroelectric energy storage ceramic for high energy storage performance scene and preparation method of lead-based anti-ferroelectric energy storage ceramic

    CN118026675A